2016
DOI: 10.1108/ijshe-05-2014-0075
|View full text |Cite
|
Sign up to set email alerts
|

Campus sustainability governance in Canada

Abstract: Purpose – This paper aims to provide an overview of a content analysis of sustainability policies from Canadian post-secondary education institutions. The paper reports findings on the orientations to sustainability evident in the policies; references to other policies within the documents; and other key themes on how sustainability is engaged in the policies in relation to overall governance, education, operations, research and community outreach. Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 19 publications
1
31
1
1
Order By: Relevance
“…This trend is prominent in the higher education sector (Vaughter et al, 2016), although here as elsewhere, research has found that institutions are often keener on signing "sustainability" declarations than on crafting accordant policies, much less thoroughly implementing them (Beveridge et al, 2015). That being noted, when a commitment to environmental responsibility expressly exists in one or more official identity statements, this offers leverage to communication professionals and other advocates championing a particular sustainability campaign.…”
Section: The Framework As Part Ofmentioning
confidence: 84%
See 1 more Smart Citation
“…This trend is prominent in the higher education sector (Vaughter et al, 2016), although here as elsewhere, research has found that institutions are often keener on signing "sustainability" declarations than on crafting accordant policies, much less thoroughly implementing them (Beveridge et al, 2015). That being noted, when a commitment to environmental responsibility expressly exists in one or more official identity statements, this offers leverage to communication professionals and other advocates championing a particular sustainability campaign.…”
Section: The Framework As Part Ofmentioning
confidence: 84%
“…In recent years, it has become increasingly common for organizations of all types to affirm their broader societal obligations, often by way of CSR ("corporate social responsibility") declarations and metrics. Such avowals frequently include environmental stewardship, which is frequently couched in sometimesbroader terms of "sustainability" (Scandelius & Cohen, 2016;Vaughter, McKenzie, Lidstone, & Wright, 2016).…”
Section: The Framework As Part Ofmentioning
confidence: 99%
“…The examination shows certain processes often begin in the course of informal activities [20] leading to an incremental incorporation [7], flanked by participatory processes, management frameworks, or guidelines, and driven by top level support, clear objectives, monitoring, and an institutional framing [7]. Mission statements [54] defining a certain policy [57] with transparent objectives, clear processes, monitoring, and communication patterns [58] promote a culture of social responsibility [7]. Human Resource Management functions as a critical success factor by providing the necessary resources [16] and spurring organizational change and commitment.…”
Section: Content Analysismentioning
confidence: 99%
“…A seguir apresenta-se alguns exemplos de como estruturado o curso de Engenharia de Produção em diferentes países. Norback et al(2010), Kennedy (1996) No Canadá os cursos de engenharia de produção (Alsaidan & Zhang, 2017) (Vaughter et al, 2016) seguem uma estrutura similar à dos melhores dos Estados Unidos (Dmochowski et al, 2016), com o diferencial de que possuírem em sua ementa disciplinas voltadas a diversos fatores humanos, como psicológicos, percepção sensorial, desempenho humano em funções específicas, habilidade de processamento de informações por pessoas e comportamento das pessoas. Através desses estudos pode-se, por exemplo, dizer onde os botões de um painel de controle devem ser alocados para a diminuição da chance de erro humano.…”
Section: Introductionunclassified